Preservation of Involved Teeth Associated with Large Dentigerous Cysts. (28th October 2014) - Guven, Yeliz; Kasimoglu, Yelda; Soluk Tekkesin, Merva; Ulug, Dicle; Cankaya, Abdulkadir Burak; Tuna, Elif Bahar; Gencay, Koray; Aktoren, Oya
Abstract : Dentigerous cysts (DCs) are benign odontogenic cysts that are associated with the crowns of permanent teeth. The purpose of this study is to describe the management of DCs in four children. Four boys aged between 7 and 9 years were referred to our clinics with the complaints of intraoral alveolar swelling or facial asymmetry on the affected area. The panoramic radiographies showed large, well-defined radiolucent lesions associated with the deciduous teeth and displaced tooth buds. The treatment consisted of the extraction of the involved deciduous tooth and marsupialization of the cyst to allow eruption of the permanent tooth. Permanent teeth displaced by the DCs in three cases erupted spontaneously within one-year period. The case with horizontally displaced permanent tooth was managed by replantation. This is the first time that underlying permanent tooth in a DC case was intentionally replanted.